Assessment of patients’ and caregivers’ informational and decisional needs for left ventricular assist device placement: Implications for informed consent and shared decision-making - Blumenthal-Barby, Jennifer S.; Kostick, Kristin M.; Delgado, Estevan D.; Volk, Robert J.; Kaplan, Holland M.; Wilhelms, L.A.; McCurdy, Sheryl A.; Estep, Jerry D.; Loebe, Matthias; Bruce, Courtenay R. (The Journal of heart and lung transplantation, 2015)
Several organizations have underscored the crucial need for patient-centered decision tools to enhance shared decision-making in advanced heart failure. The purpose of this study was to investigate the decision-making process and informational and decisional needs of patients and their caregivers regarding left ventricular assist device (LVAD) placement. In-depth, structured interviews with LVAD patients, candidates and caregivers (spouse, family members) (n = 45) were conducted. We also administered a Decisional Regret Scale. Participants reported LVAD decision-making to be quick and reflexive (n = 30), and deferred heavily to clinicians (n = 22). They did not perceive themselves as having a real choice (n = 28). The 2 most prevalent informational domains that participants identified were lifestyle issues (23 items), followed by technical (drive-line, battery) issues (14 items). Participants easily and clearly identified their values: life extension; family; and mobility. Participants reported the need to meet other patients and caregivers before device placement (n = 31), and to have an involved caregiver (n = 28) to synthesize information. Some participants demonstrated a lack of clarity regarding transplant probability: 9 of 15 patients described themselves as on a transplant trajectory, yet 7 of these were destination therapy patients. Finally, we found that decisional regret scores were low (1.307). Informed consent and shared-decision making should: (a) help patients offered highly invasive technologies for life-threatening disease get past the initial “anything to avoid thinking about death” reaction and make a more informed decision; (b) clarify transplant status; and (c) focus on lifestyle and technical issues, as patients have the most informational needs in these domains.